Standardized Digital Colposcopy with Dynamic Spectral Imaging for Conservative Patient Management - Angelika Kaufmann; Christina Founta; Emmanouil Papagiannakis; Raj Naik; Ann Fisher (Hindawi Limited, 2017)
Background. Colposcopy is subjective and management of young patients with high-grade disease is challenging, as treatments may impair subsequent pregnancies and adversely affect obstetric outcomes. Conservative management of selected patients is becoming more popular amongst clinicians; however it requires accurate assessment and documentation. Novel adjunctive technologies for colposcopy could improve patient care and help individualize management decisions by introducing standardization, increasing sensitivity, and improving documentation. Case. A nulliparous 27-year-old woman planning pregnancy underwent colposcopy following high-grade cytology. The colposcopic impression was of low-grade changes, whilst the Dynamic Spectral Imaging (DSI) map of the cervix suggested potential high-grade. A DSI-directed biopsy confirmed CIN2. At follow-up, both colposcopy and DSI were suggestive of low-grade disease only, and image comparison confirmed the absence of previously present acetowhite epithelium areas. Histology of the transformation zone following excisional treatment, as per patient's choice, showed no high-grade changes. Conclusion. Digital colposcopy with DSI mapping helps standardize colposcopic examinations, increase diagnostic accuracy, and monitor cervical changes over time, improving patient care. When used for longitudinal tracking of disease and when it confirms a negative colposcopy, it can help towards avoiding overtreatment and hence decrease morbidity related to cervical excision.